Enhancing digital competence through ICT training for custodial staff at FPTI UPI - Sri Rahayu; Dedi Purwanto; Danny Meirawan; Sukadi Sukadi; Dewi Ayu Sofia; Hanifah Indah Rahmawati; Rieske Iswardhany (Universitas Pendidikan Indonesia, 2025)
This community service project aims to enhance Information and Communication Technology (ICT) skills among cleaning staff at the Faculty of Technical and Industrial Education (FPTI), Universitas Pendidikan Indonesia (UPI). The primary objective is to improve both technical and soft skills to increase the efficiency, service quality, and professionalism of custodial personnel. Limited ICT proficiency has been identified as a barrier to effective campus cleaning operations, especially in a digitally transforming environment. To address this, the project implemented a structured program comprising needs assessment, targeted training sessions, intensive mentoring, and performance evaluation through pre-test and post-test instruments. The results indicate a significant increase in participants’ ability to use digital tools, leading to better task management and improved motivation. Despite these positive outcomes, challenges remain in maintaining consistent service standards and effective time management. Overall, the project highlights the importance of continuous ICT capacity-building efforts as a strategic approach to strengthening non-academic support functions in higher education institutions. Abstrak Program pengabdian kepada masyarakat ini bertujuan meningkatkan keterampilan Teknologi Informasi dan Komunikasi (TIK) bagi petugas kebersihan di Fakultas Pendidikan Teknik dan Industri (FPTI), Universitas Pendidikan Indonesia (UPI). Kegiatan ini menitikberatkan pada penguatan keterampilan teknis dan soft skills demi mendorong efisiensi kerja, peningkatan kualitas layanan, serta penguatan profesionalisme tenaga kebersihan. Literasi TIK yang masih rendah seringkali menjadi penghambat dalam mendukung digitalisasi operasional kampus. Untuk menjawab tantangan tersebut, serangkaian tahapan telah disusun, dimulai dari asesmen kebutuhan, pelatihan berbasis kompetensi, pendampingan secara intensif, hingga evaluasi melalui pendekatan pre-test dan post-test. Implementasi program menunjukkan peningkatan signifikan dalam penguasaan perangkat digital, yang berdampak pada pengelolaan tugas secara lebih efisien dan meningkatnya motivasi kerja peserta. Di balik capaian tersebut, tantangan terkait konsistensi mutu layanan serta manajemen waktu tetap perlu mendapat perhatian lebih lanjut. Secara umum, kegiatan ini menegaskan urgensi pengembangan kapasitas digital berkelanjutan, terutama dalam memperkuat peran strategis tenaga nonakademik sebagai bagian integral dari proses transformasi digital di lingkungan pendidikan tinggi. Kata Kunci: kualitas kerja; pelatihan tik; petugas kebersihan